Persepsi Guru Sekolah Dasar Tentang Integrasi Steam Dan Educulture Dalam Pembelajaran Terpadu - Siti Raihan; Reza Ma’ruf; Amir Pada; Teguh Putra Gusal; Saprizal Saprizal (CENDEKIA PENDIDIKAN, 2026)
This study aims to analyze elementary school teachers' perceptions of integrating the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach and Educulture (culture-based education) in integrated learning. The research employed a mixed-methods approach with an explanatory sequential design, involving 30 teachers and 5 principals from 7 elementary schools in Makassar City. Quantitative data were collected through a questionnaire measuring three dimensions of perception (knowledge, attitudes, and expectations/concerns), while qualitative data were obtained through semi-structured interviews with principals. The results showed that teachers' knowledge of local wisdom was excellent (93-97%), but their understanding of STEAM (73%) and Educulture (53%) still needs improvement. Teachers' attitudes toward integrating STEAM and Educulture were highly positive (average above 90%), with all teachers agreeing that local culture is important to be introduced in schools. The main needs of teachers were integrated module examples (48%), structured training (32%), and learning communities (20%), while the main concerns included administrative burdens (90%), time constraints (87%), and incomplete curriculum material (83%). The gap between appreciation for local wisdom and the ability to systematically integrate it into STEAM was the most significant finding. This study concludes that teachers have strong social capital in the form of positive attitudes and good cultural knowledge but require concrete support in the form of teaching modules, applicable training, and supportive policies to achieve optimal integration of STEAM and Educulture in elementary schools.